Efficacy of CARVYKTI in CARTITUDE-4 versus other conventional treatment regimens for lenalidomide-refractory multiple myeloma using inverse probability of treatment weighting - Winfried Alsdorf; Joris Diels; Francesca Ghilotti; Joao Mendes; Teresa Hernando; Patricia Cost; Jordan M Schecter; Nikoletta Lendvai; Nitin Patel; Ana Triguero; Margherita Ursi (Becaris Publishing Limited, 2024)
Aim: The phase III randomized controlled trial (RCT) CARTITUDE-4 (NCT04181827) demonstrated superiority of CARVYKTI (ciltacabtagene autoleucel; cilta-cel) over daratumumab, pomalidomide and dexamethasone (DPd) and pomalidomide, bortezomib and dexamethasone (PVd) for relapsed/refractory multiple myeloma (RRMM) patients who have received one to three prior line(s) of therapy (LOT[s]) including an immunomodulatory agent and a proteasome inhibitor, and are refractory to lenalidomide. These analyses estimate the relative efficacy between cilta-cel and other common treatment regimens, for which no direct comparative evidence is available. Materials & methods: Patient data were available from the CARTITUDE-4, CASTOR, CANDOR and APOLLO RCTs. Imbalances between cohorts on key patient characteristics were adjusted for using inverse probability of treatment weighting (IPTW). Relative efficacies were estimated with response rate ratios (RRs) and 95% confidence intervals (CIs) for overall response rate (ORR), very good partial response or better rate (≥VGPR) and complete response or better rate (≥CR), and with hazard ratios (HRs) and 95% CIs for progression-free survival (PFS). Sensitivity analyses using different analytical methods and additional covariates were explored. Results: Key characteristics were well balanced across cohorts after IPTW. Cilta-cel showed statistically significant benefit in PFS (HRs: 0.11-0.51), ≥VGPR (RRs: 1.51-5.13) and ≥CR (RRs: 2.90-35.24) versus all comparators, and statistically significant improvements in ORR over most comparator regimens (RRs: 1.22-1.90). Results were consistent across sensitivity analyses. Conclusion: Cilta-cel demonstrated benefit over other common treatment regimens, highlighting its potential to become a new standard of care option for lenalidomide-refractory RRMM patients with one to three prior LOT(s). These comparisons help to demonstrate the improved efficacy of cilta-cel in countries where the standard of care may differ from DPd/PVd.